Perancangan Data Warehouse Penjualan Minimarket XYZ Menggunakan Kimball Modeling dan Analisis OLAP - Ketut Agus Wikananda; Muhammad Raka Nur Habibi; Andri Wijaya (GLOBAL SCIENTS PUBLISHER, 2025)
Minimarkets generate large volumes of transaction data every day that have not been fully utilized for business analysis. This study aims to design a minimarket sales data warehouse using the Kimball method and to conduct OLAP analysis using RapidMiner. The steps carried out include identifying requirements, designing a dimensional model based on a star schema, performing ETL processes, and conducting OLAP analysis. Sales data are processed into a fact table and several dimension tables. The analysis results indicate that the data warehouse can display sales information multidimensionally based on time, product, and region, which is useful for managerial decision-making.